The Impact of Supplier-Customer Collaboration on Sustainability-Oriented Capability: The Mediating Role of Communication Effectiveness and Technology Adoption in Micro-Enterprises - Gronphet, Seree; Onputtha, Suraporn (Bright Publisher, 2025)
With many businesses transforming digitally to lead future trends driven by sustainability, supplier-customer collaboration is key in empowering MSMEs. Nevertheless, effective collaborative practices remain challenging for MSMEs due to resource constraints and operational limitations. This study examines the mediating role of communication effectiveness and technology adoption in the relationship between supplier-customer collaboration and sustainability capabilities. Data was collected from 400 MSMEs in Bangkok and metropolitan area, Thailand, and analyzed using partial least squares-structural equation modeling (PLS-SEM). Results indicate that supplier-customer collaboration positively influences sustainability capability directly (β=0.345, p 0.001) and indirectly through communication effectiveness (β=0.370, p 0.001) and technology adoption (β=0.043, p 0.001). Effectiveness of communication appeared to be the superior mediator, providing evidence that the impact of technology adoption is less influential in resource-constrained environments. The study’s novelty lies in its focus on micro-enterprises’ unique constraints and the creation of a contextualized framework that prioritizes effective communication over technological investments, challenging conventional sustainability models derived from large organizations and offering context-specific policy recommendations for enhancing micro-enterprise sustainability in developing economies.